Pembuatan Keputusan Etis pada Mahasiswa: Tema-Tema, Faktor-Faktor yang Memengaruhi dan Strategi Mengatasi Dilema - Retno Kumolohadi; Frieda Mangunsong; Julia Suleeman (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2020)
The aimed of this study was to explore ethical and unethical decisions themes, determinant factors, and strategies for coping the dilemma. The method used in this research was qualitative with phenomenology approach. Data were collected by a semi open ended questionnaire (N=124), and focus group discussions (N=14). The results showed ethical themes regarding problems with attendance in class and academic assignments, problems with parents, problems with friend, and issues of public order. The dominant personal factors were moral character and religiosity. While situational factors included obedience to authority, fear of other people's dislike, conformity, sanctions, and opportunity. Coping the ethical dilemma were focused on one or more strategies which consist of risks and consequences, legal and religious principles, advice from others (friends, parents), and character. This research has theoretical and practical implications for the development of ethical decision-making model as input in the teaching and learning process in higher education.